TINJAUAN TERHADAP INDEPENDENSI KOMISI POLISI NASIONAL DALAM PERSPEKTIF LEMBAGA NEGARA INDEPENDEN - Nasrullah, Nasrullah (Universitas Ekasakti, 2023)
The National Police Commission (Kompolnas) is one of the state institutions whose functions and authorities are quite strategic in assisting the president in formulating the vision of the national police. Apart from being an institution that is expected to become an external